2005
DOI: 10.1088/0964-1726/15/1/032
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fiber volume fraction and aspect ratio on the creation of internal stress in the matrix and deformation for short-fiber shape memory alloy composite

Abstract: In recent years, some researchers have studied about shape memory alloy composites (SMACs) which consist of a shape memory alloy (SMA) reinforcement and polymer or metal matrix. In particular, considerable attention has been paid to the creation of internal stress in a matrix of SMAC. Internal stress in a matrix can be created when a deformed SMA fiber recovers its original shape in a composite. On the other hand, deformation of the composite appears when internal stress is created in matrix. Therefore, an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…The presented values are the desired aspect ratios for SMA/epoxy composites. This result is consistent with the results reported by Murasawa et al 28 They reported that the SMA wire aspect ratio should be greater than 25 for effective short SMA wire composites.…”
Section: Vibration Resultssupporting
confidence: 93%
“…The presented values are the desired aspect ratios for SMA/epoxy composites. This result is consistent with the results reported by Murasawa et al 28 They reported that the SMA wire aspect ratio should be greater than 25 for effective short SMA wire composites.…”
Section: Vibration Resultssupporting
confidence: 93%
“…The dependence of rigidity and strength on temperature is therefore quite opposite between SMA and SMP elements. If the composite materials with SMA and SMP having different properties are developed, the new actuation properties of the material can be obtained (Murasawa et al 2004(Murasawa et al , 2006Tobushi 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate substantial variation in stress distribution profiles for different activation and loading scenarios. In the work of Murasawa et al [306], a constitutive relationship was proposed for SMA composites based on the shear-lag model. The main conclusions of this work were the following: composite shrinkage and compressive residual stress in the matrix increase with increasing aspect ratio and fiber volume fraction after heating.…”
Section: Structural Analysis Toolsmentioning
confidence: 99%